2011
DOI: 10.1080/1331677x.2011.11517466
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Financial Openness on Financial Development, Growth and Volatility in Turkey: Evidence From the Ardl Bounds Tests

Abstract: The aim of this paper is to investigate the impact of financial openness on financial development, growth and output volatility in Turkey. Results of the bounds test reveal that financial openness is in a long run equilibrium relationship with financial development, growth and output volatility. Granger causality tests disclose the existence of unidirectional causality from financial development to financial openness in the long run and from financial openness to output volatility in the short run. Yet, no Gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
3
2
0
1
Order By: Relevance
“…Moreover, the maximum eigenvalue (95.84860) is higher than the critical value (46.23142) at 5% as well. These results are supported by (Ajie et al, 2019;Dinh et al, 2019;Egbetunde and Akinlo, 2015;Ersoy, 2011;and Klasra, 2011).…”
Section: Johansen Co-integrationsupporting
confidence: 71%
“…Moreover, the maximum eigenvalue (95.84860) is higher than the critical value (46.23142) at 5% as well. These results are supported by (Ajie et al, 2019;Dinh et al, 2019;Egbetunde and Akinlo, 2015;Ersoy, 2011;and Klasra, 2011).…”
Section: Johansen Co-integrationsupporting
confidence: 71%
“…The findings of the current study are also consistent with the findings by Tongurai and Vithessonthi (2023), Umutlu et al (2020), Ersoy (2011) and Zhang et al (2015) who also found a positive relationship between financial openness and financial development. Trade openness, real gross domestic product, real interest rate and government expenditure were all statistically significant at 1% alpha level with the exception of inflation that is significant at 5% alpha level.…”
Section: Long-run Results (Fsdi Is the Dependent Variable)supporting
confidence: 93%
“…Ersoy (2011) investigated the impact of financial openness on financial development, growth and volatility in Turkey: evidence from the ARDL bounds tests. The bounds test results indicate that financial openness is in a long-run equilibrium relationship with financial development, growth and output volatility in Turkey.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…To control and check the ARDL specification, the empirical sources such as Feridun et al . (), Acaravci (), Feridun (), Yazici and Islam (), Ersoy (), Erdem and Tugcu (), Bildirici and Kayikci (), Insel and Kayikci (), Tang (), Joader et al . () were analysed in deep.…”
Section: Methodsmentioning
confidence: 99%